(untitled) (Papeles, 2023)
This paper addresses the legal, social and cultural implications generated by the impact of the Zonda, an intense and warm wind that occurs, paradoxically, during the winter in the Cuyo region. The study is interdisciplinary in nature, analyzing jurisprudence in the light of local literary works. In the sentences, the legal institutes are linked, fundamentally, to the Law of Damages. At par; from the literary works of the narrative genre (legends of native peoples) and didactic (teaching and dissemination) worldviews emerge that understand differently the relationship of the human being and this phenomenon of nature. From the conjunction of knowledge, it is expected to achieve a different approach, which allows building a look that overcomes the reductionism that creates the Zonda, author of the violence suffered by the inhabitants.